Modern aspect of formation of training process of female sportsmen - Viacheslav Mulyk (Kharkiv State Academy of Physical Culture, 2016)
Purpose: to consider a question of formation of training process of female sportsmen. Material & Methods: methods of theoretical analysis and generalization of scientific information, systems analysis were used in the research. Results: modern approaches relatively to the features of formation of training process of young and skilled female sportsmen are presented; the structure of formation of basic mezocycle taking into account the phases of ovarian-menstrual cycle and its application in an annual macrocycle by skilled female sportsmen is given. Conclusions: it is determined that it is necessary to distribute physical exercises according to ovarian-menstrual cycle in the training process of young female sportsmen in an annual macrocycle. At the same time registration of loads in the trainings of skilled female sportsmen should be accomplished in basic mezocycles.